The Effects of ESL Immersion and Proficiency on Learners’ Pronunciation Development - Kostromitina, Maria; Kang, Okim (Frontiers in Communication, 2021)
Despite the efforts of existing studies in the domain of L2 phonology to examine ESL learners’ pronunciation development, little research has comprehensively demonstrated ESL learners’ pronunciation improvement in academic immersion contexts. Similarly, few studies have focused on learners’ proficiency levels linked to their developmental success. The current exploratory study investigated the changes of learners’ pronunciation constructs as a result of their ESL program. Seventy-five newly arrived ESL students (25 in each proficiency; beginner, intermediate, and advanced) enrolled in an Intensive English Program in the U.S. provided their speech responses (to the placement and exit tests from the program). One hundred fifty speaking samples were linguistically analyzed for the following suprasegmental features: fluency (speech rates and pauses) and prosody (prominence and pitch range). Segmental features were analyzed by employing a functional load approach with randomly selected 90 speech files. Findings revealed different developmental patterns among phonological features and proficiency levels; that is, the upper level learners improved more in fluency and prominence than the lower-level learners. Segmental changes were minimal, suggesting that both high functional and low functional load sounds involve a complex process in learning. Overall findings provide important implications for ESL curriculum planning and development: (1) intonation acquisition can be difficult; (2) skill improvement differs by proficiency level; and (3) level specific curriculum may be needed.